2015
DOI: 10.1021/acs.jafc.5b04119
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins Deoxynivalenol and Fumonisins Alter the Extrinsic Component of Intestinal Barrier in Broiler Chickens

Abstract: Deoxynivalenol (DON) and fumonisins (FBs) are secondary metabolites produced by Fusarium fungi that frequently contaminate broiler feed. The aim of this study was to investigate the impact of DON and/or FBs on the intestinal barrier in broiler chickens, more specifically on the mucus layer and antioxidative response to oxidative stress. One-day-old broiler chicks were divided into four groups, each consisting of eight pens of seven birds each, and were fed for 15 days either a control diet, a DON-contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 66 publications
3
64
1
Order By: Relevance
“…This effect on nutrient transporters has already been described during infection with E. maxima [34]. In unchallenged birds, our results are in agreement with Antonissen et al [10] that also showed that the Sa/So ratios in plasma of birds fed FB alone or in combination with DON were the same. Indeed, it was hypothesized that the known increase of paracellular permeability by DON (through its effects on tight junctions) could at the same time increase the passage of other toxics, such as FB.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This effect on nutrient transporters has already been described during infection with E. maxima [34]. In unchallenged birds, our results are in agreement with Antonissen et al [10] that also showed that the Sa/So ratios in plasma of birds fed FB alone or in combination with DON were the same. Indeed, it was hypothesized that the known increase of paracellular permeability by DON (through its effects on tight junctions) could at the same time increase the passage of other toxics, such as FB.…”
Section: Discussionsupporting
confidence: 93%
“…Poultry have long-been considered relatively resistant to mycotoxins, especially to toxins from Fusarium . However, very recent investigations have shown that concentrations of mycotoxins below the EU and US limits or at concentrations lower than those that would cause overt clinical mycotoxicosis, may significantly affect the performance and health of birds [5,6,7,8,9,10]. Many reasons may account for these new findings.…”
Section: Introductionmentioning
confidence: 99%
“…Methionine deficiency in the pancreas may promote dysfunctions of pancreas in similar to those in rodents treated with CDE diet. Consistent with this idea, FB1 treatment resulted in the up-regulation of the intestinal brush border transporter B0AT and the basolateral transporter y+LAT1 in newborn chickens, suggesting the demand of an increased intracellular uptake of neutral amino acids such as methionine 148) .…”
Section: Pancreatic Phospholipase Functionmentioning
confidence: 56%
“…Feeding FB-containing diet (FB1 + FB2 25.4 mg/kg feed) for 15 days to chickens resulted in altered glycosylation of mucin and in a decreased level of mucin 2 mRNA in the duodenum 148) . In addition, specific mRNA level of basolateral zinc transporter (ZnT1) was reduced in jejunum of FB-treated chickens 148) , which may contribute to maintain the zinc ion in brush border.…”
Section: Intestinal Membrane Alteration and Zincdeficiencymentioning
confidence: 99%
See 1 more Smart Citation